Diagnosis of creole seed production and storage techniques in rural settlements in Aparecida, Paraíba, Brazil (Research, Society and Development, 2020)
Producing and storing Creole seeds is a practice adopted by many farming families that enables social and environmental gains and maintains the cultural identity of traditional rural communities. The objective of this work was to evaluate the ways of production and storage of creole seeds by farming families living in rural settlements of the agrarian reform in Aparecida - PB. The research was qualitative and quantitative, using as a tool for data collection a semi-structured questionnaire about the social profile of farmers, seed production and storage techniques and a listing of commonly used seeds. Based on the observed data, the social and environmental importance of farmers' maintenance of Creole seeds can be highlighted. It was found also that the forms of production are agro-ecological character in manual sowing and planting intercropping systems. The preparation of the seeds is handmade and consists of the visual selection of the seeds, followed by drying in the open and later storage in recycled PET bottles.